Predictors of sleep modifiable factors and the correlation with non-suicidal self-injury: the important role of problematic mobile phone use and mental health - Li Zhu; Keyan Hu; Qingqing Kang; Yijing Chen; Li Gong; Qiu Zhang; Yi Zhang (BMC Psychiatry)
Abstract Backgrounds Non-suicidal self-injury (NSSI) has long affected people's lives and is an important and serious public health issue, especially among college students. This study aims to identify modifiable factors, including problematic mobile phone use (PMPU) and mental health (MH), etc. Only a few studies have mentioned the correlation between PMPU and NSSI, this study focus on its association with suicide, and whether this association is moderated by chronotype and MH needs to be confirmed by research. Methods A cross-sectional study design investigated the association between PMPU, chronotype and MH and NSSI. We collected information from participants using an electronic questionnaire that included general demographics, PMPU, NSSI, and sleep-related variables (chronotype, weekday and weekend sleep duration). Participants completed standardized questionnaires, including mobile phone addiction tendency scale (MPATS) for PMPU, the Morningness-Eveningness Questionnaire (MEQ) for chronotype, Patient Health Questionnaire (PHQ-9) for depression symptoms, Generalized Anxiety Scale (GAD-7) for anxiety symptoms, and the non-suicidal self-injury (NSSI) for suicide risk. A multivariable linear regression model measure these variables, and moderation model which using the PROCESS method examined the relationship of PMPU, chronotype and MH and NSSI. Results A total of 5639 adolescents were included in the study, with a mean age of 19.64 [± 0.90] years), and 46.3% of the participants were male. The prevalence of NSSI was 12.1%, in multivariate linear regression, high levels of PMPU (β = 0.362), eveningness (β = 0.665), depression (β = 1.183), and anxiety (β = 1.308) were all associated with higher NSSI, indicating a significant association. In the analysis results of moderation, chronotype and MH also moderated the relationship between PMPU and NSSI, indicating that there was a relationship between PMPU, chronotype, MH and NSSI. Conclusions This study highlights the important role of PMPU and mental health in predicting NSSI. Interventions targeting these modifiable factors may help reduce the prevalence of NSSI among young adults. Improving sleep hygiene, reducing mobile phone abuse, and providing appropriate psychological support are effective strategies to prevent NSSI. Educational institutions and society should strengthen guidance on the proper use of digital media by young people, especially among college students, promote healthy lifestyles, and establish early identification and support systems to help those individuals at risk.